Rancang Bangun Mesin Pemotong Pipa Dengan Pergerakan Torch Otomatis Untuk Optimasi Proses Plasma Cutting - Anggun Pamuji; Pujono (Politeknik Negeri Cilacap, 2020)
The development of the industrial world that is increasingly making the production process in an industry or factory requires increasingly developing technology and materials and tools that are easy to obtain so that the production process can run smoothly. One component needed in the industrial world is a material in the form of a pipe. Some industries still do the pipe cutting process using oxy acetylene welding which still uses hand and saw saws. This is certainly not effective because the pipes have different size and thickness. To cut the pipe using oxy acetylene welding will produce less neat pieces because the process is still manual by hand and must rotate the pipe, so we need a tool to facilitate the cutting process. Pipe cutting machine using plasma cutting is a machine made to facilitate the pipe cutting process. The process of cutting pipes is cutting tools that move around to produce pieces of pipe. With this machine, it can help speed up students in the process of cutting pipes without having to rotate the pipe to be cut. The purpose of the skeletal design of the pipe cutting machine using plasma cutting is to count the elements of the machine, determine the frame of the machine, determine the design concept of the machine and make the design of the draw frame. In making this machine the author uses the design method approach of VDI 222, drawing software using Solidworks 2017 and working drawings using ISO standards. The results of the concept design evaluation decision are, the framework uses 40 x 40 x 3mm hollow iron with an estimated production time used is 15.32 hours or equal to 2 working days if it is done in 1 day for 8 hours. Then the bill of material in making the frame on this machine spent 53 parts. The best cutting results are obtained from cutting 8 mm thick pipes with a speed of 10 rpm. So from the planning, the framework on the pipe cutting machine using plasma cutting, can function properly. so we need a tool to facilitate the cutting process.